Translation Studies in China The State of the Art - Han, Ziman; Li, Defeng (New Frontiers in Translation Studies, 2019)
This book features the latest research on translation by a dozen leading scholars of translation studies in China. The themes discussed are diverse, and include: translation policy, literary translation, medical translation, corpus translation studies, teaching translation, translation technologies, media translation, interpreting studies and so on. The contributors are all respected experts on their respective topics. The book reflects the state-of-the-art of translation studies in China, and offers a unique window on the latest thoughts on translation there.